The trade finance program and its role in lifting impediments to trade. (Metro Manila, Philippines Asian Development Bank, 2017)
This brief looks at the trade enhancement potential of fintech, issues that need to be addressed to bridge gaps in trade finance, and implications for banks around the world.
Keywords: Finance -- Government policy -- Asia..; Financial institutions -- Developing countries; Banks and banking -- Developing countries; Electronic books